Sus sp. DNA encoding Cyt b gene detection test on soft gel candy samples using PCR method - Latifatoel Chilmi; Tri Susilowati; Yuanita Rachmawati; Saiku Rokhim; Inggrit Tyautari (Universitas Airlangga, 2021)
Softgel candy is soft-textured confectionery processed by the addition of several components such as gum, pectin, starch and gelatin, to obtain a supple product and packed after aging treatment first. Gelatin is one of the main components in the manufacture of soft candy derived from the hydrolysis of collagen connective tissue and animal bone that serves as the nature of gelling agents, stabilizers or emulsifiers. However, the gelatin used in products not yet labeled halal Indonesian Council of Ulama (MUI) is particularly vulnerable to pork gelatin, since pork gelatin is cheaper than cattle. The purpose of this study was to test the contaminants of pig DNA on 17 samples of soft candles not labeled halal MUI. This research used Polymerase Chain Reaction (PCR) method. Seventeen samples were isolated by DNA, then spectrophotometry was performed, followed by PCR. The PCR product is run electrophoresis. Visualize the DNA with a UV gel documentation. Primer used is primer gene encoding cyt b DNA pork. Results showed that 17 samples were negative contaminants, while the positive control of pork showed a DNA band of 149 bp. This shows that Softgel Candy 17 samples do not contain pork gelatin.